Modeling microstructural effects in dilatational plasticity of polycrystalline materials - Lebensohn, Ricardo A. (2012)
In a recent paper [1] we presented a new constitutive model for the viscoplastic response of polycrystalline aggregates accounting for local anisotropy induced by crystal plasticity and dilatational effects associated with the presence of intergranular cavities. In this contribution we provide a summary of our findings, as well as previously unpublished details of the numerical algorithm underlying this novel formulation. The formulation is based on homogenization and captures microstructural effects on the dilatational plastic behavior of polycrystalline materials. These effects are relevant to many engineering problems in which the presence of cavities embedded in a heterogeneous and anisotropic polycrystalline matrix must be accounted for, and for which standard polycrystalline models of incompressible plasticity, or dilatational plasticity formulations for voided materials with uniform properties of the matrix, have been proven to be insufficient. The present approach makes use of variational linearcomparison homogenization methods to develop constitutive models simultaneously accounting for texture of the matrix, porosity and average pore shape and orientation. The predictions of the models are compared with full-field numerical simulations based on fast Fourier transforms to study the influence of different microstructural features (e.g. overall porosity, single-crystal anisotropy, etc.) and triaxiality on the dilatational viscoplastic behavior of voided fcc polycrystals.